The effectiveness of current law and its application in protecting the wildlife of west Malaysia / Catherine Nicholas … [et al.] - Nicholas, Catherine; Samuel, Christie Bulan; Zainuddin, Faisal Nazrin; Halili, Jasmine (2006)
In recent times, there have been many reported cases of such barbaric killings of wildlife and inadequate punishment sanctioned upon the offenders. This forms the basis of the research in the light of illegal animal trade, protection of wildlife and the adequacies of the legislation and execution of laws. This paper sets out to examine the sufficiency of current local laws and its enforcement in protecting Malaysian wildlife. The primary legislation that provides for wildlife in Malaysia is the Protection of Wildlife Act 1972 which is only applicable in West Malaysia, the targeted area of research. Loopholes or shortcomings of the said Act are found throughout the research and has been affirmed by most of the persons interviewed for the purpose of this paper. Furthermore, there are such non-governmental organizations (NGOs) as the World Wide Fund for Nature (WWF) that have a say in the matter. However, problems may surface as to the matter of non-jurisdiction or limitations of power to compel or take legal action on the part of NGOs and thus, the power is in the state's hands, where ruling is based on the old legislation which may have been efficient in earlier days, but it would be absurd to say the same for its implications 30 years down the road. At the time of research however, the writers were pleased to hear that the Act is soon to be renewed. It has been said that the title in itself could be altered, with what is believed to be additional provisions and amendments supplying to a wider scope of laws. Therefore, it may be rightfully presumed that the current Protection of Wildlife Act is questionable and rather not effective in its content and enforcement in providing protection and curbing such crimes against the wildlife of West Malaysia.